Pengaruh Temuan Audit, Kualitas Auditor Internal, dan Tindak Lanjut Pemeriksaan terhadap Pengungkapan Laporan Keuangan PT ASABRI - Emilia Gustini; Tria Aprilia (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze the influence of audit findings, internal auditor quality, and audit follow-up on financial statement disclosure at PT ASABRI (Persero) South Sumatra. This study employed a quantitative approach with a causal associative research design. Data were obtained from 29 respondents selected using purposive sampling and collected through questionnaires. Data analysis was performed using multiple linear regression with SPSS version 31.1 software. The results indicate that partially, audit findings, internal auditor quality, and audit follow-up do not significantly influence financial statement disclosure. However, simultaneously, these three variables significantly influence financial statement disclosure at PT ASABRI (Persero) South Sumatra. The coefficient of determination indicates that audit findings, internal auditor quality, and audit follow-up explain 47.4% of the variation in financial statement disclosure, while the remainder is influenced by other variables outside the research model. The results of this study indicate that the management of audit findings, improving the quality of internal auditors, and the effectiveness of audit follow-up collectively play a significant role in enhancing the transparency and accountability of financial statement disclosure.